Improving Science Process Skill though Guided Inquiry and Performance Assesment - Siti Mayang Mangurai (EDUSAINS, 2017)
Abstract This research aims to understand the increase in skill the process of science students with a guided inquiry model and performance assessment and the implementation of guided inquiry model and performance assessment to students of class XI IPA  Christian High School 1 Salatiga . Skills of the research process are studied consisting of observing, hypothesizing, questioning, applying concepts, communicating, and practicing with minimum criteria for psychomotor criteria for 73. The type of research used is classroom action research with data triangulation research technique, in the form of questionnaire instrument, interview sheet, observation sheet, student performance assessment result, and supporting data in the form of documentation. The results showed that the results of the students' science process skills experienced an increase in each cycle. Guided inquiry models also familiarize students to play an active role in all learning activities and practicum conducted by students, so that students not only understand the material but also skillfully using laboratory tools. Keywords: guided inquiry; KPS; performance assessment; student. Abstrak Peneliitian ini  bertujuan untuk mengetahui peningkatan keterampilan proses sains siswa dengan model inkuiri terbimbing dan performance assessment serta penerapan model inkuiri terbimbing dan performance assessment pada siswa kelas XI IPA I SMA Kristen 1 Salatiga. Keterampilan proses sains yang diteliti terdiri dari keterampilan mengamati, berhipotesis, menanya, menerapkan konsep, berkomunikasi, dan melakukan praktikum dengan kriteria ketuntasan minimal untuk psikomotorik sebesar 73. Jenis penelitian yang digunakan yaitu penelitian tindakan kelas dengan teknik penelitian triangulasi data, berupa instrumen angket, lembar wawancara, lembar observasi, hasil performance assessment siswa, dan data pendukung berupa dokumentasi. Hasil penelitian menunjukkan bahwa hasil keterampilan proses sains siswa mengalami peningkatan pada setiap siklus. Model inkuiri terbimbing juga membiasakan siswa untuk berperan aktif dalam seluruh kegiatan pembelajaran dan praktikum yang dilakukan siswa, sehingga siswa tidak hanya memahami materi tetapi juga cakap menggunakan alat-alat laboratorium. Kata kunci: inkuiri terbimbing; KPS; performance assessment; siswa. Permalink/DOI:http://dx.doi.org/10.15408/es.v9i2.7209